2015
DOI: 10.2139/ssrn.2796368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Public Investment on Economic Growth

Abstract: The study examines the relationship between Gross domestic product and public investment. Time series data for empirical investigation covers the period 1980-2009. The data has collected from Pakistan bureau of Statistics, State bank of Pakistan (SBP) and Stockholm International Peace Research Institute (SIPRI). Empirical results show, there is a positive relationship between GDP and public investment in short run. The increase in GDP causes a rapid increase in public investment. Granger causality test apply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
(19 reference statements)
1
6
0
3
Order By: Relevance
“…Similarly, investment shows the existence of strong positive and mostly significant estimates on economic growth in the SADC region. These results confirm the conclusions of other studies, such as Rabnawaz and Jafar (2015). Inflation also presents the expected sign and the variable is significant at 1st level of significance.…”
supporting
confidence: 91%
“…Similarly, investment shows the existence of strong positive and mostly significant estimates on economic growth in the SADC region. These results confirm the conclusions of other studies, such as Rabnawaz and Jafar (2015). Inflation also presents the expected sign and the variable is significant at 1st level of significance.…”
supporting
confidence: 91%
“…Investment leads to an increase in the aggregate supply by enhancing the level of domestic output, income, and employment. The aggregate demand also increases, which further enhances the level of income, employment through the multiplier effect (Rabnawaz et al, 2015). The other variables like schooling, FDI, openness, and financial development"stimulate economic growth.…”
Section: Fixed Effect Model (Fem) Resultsmentioning
confidence: 99%
“…Researchers on the linkage between internal investments and economic growth have not fully viewed relationships from economic, finance, and accounting terms perspective. In Kenya, research findings showed a positive relationship between public investments and economic growth (Maingi, 2017) as too several other studies considered (Ghani and Din, 2006;Rabnawaz and Jafar, 2015). However, there is a case of negative public investments influencing economic growth (Saidjada and Jahan, 2018) and private investments at the end in Pakistan.…”
Section: 2mentioning
confidence: 92%